Pengaruh Tindakan Mobilisasi Dini Terhadap Denyut Jantung dan Frekuensi Napas Pasien Di Ruangan ICU RSUD Prof. Dr. H. Aloei Saboe Kota Gorontalo - Lamadu, Hesti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: to identify hemodynamic instability in critical patients due to problems in heart rate and respiratory frequency can cause potential complications up to death in patients so efforts are needed to stabilize the patient's heart rate and respiratory frequency with non-pharmacological therapy with early mobilization measures. Methods: This article is pre-experimental research with one group pre-test and post-test design, The object of the study was a critical patient in the ICU room of RSUD Prof. Dr.H. AloeiSaboe. The subject of study is the subject intended to be researched by the author or the subject that is the center of attention or target of the researcher. The subjects in this case study were patients in the ICU room of RSUD Prof. Dr. H. Aloei Saboe as many as 17 respondents with the criteria of patients who did not experience severe pain, oversedation and patient guardians who were willing to be respondents. The research instrument uses observation sheets. The data were analyzed with Wilcoxon's non-parametric statistical test. Results: The results showed that heart rate before early mobilization the average heart rate value was 126.71x/ minute with a standard deviation of 19.299 and after early mobilization the average heart rate value was 99.76x/ minute with a standard deviation of 8.729. The frequency of breathing before early mobilization the average breath frequency was 24.65x/minute with a standard deviation of 4.030 and after early mobilization the average breath frequency value was 22.18x/minute with a standard deviation of 2.351. Furthermore, the p-value for heart rate is 0.001 (<α 0.05) and breath frequency is 0.010 (<α 0.05). Conclusion: There is an influence of early mobilizationmeasures on the patient's heart rate and breathing frequency in the ICU Room of RSUD Prof. Dr. H. Aloei Saboe Gorontalo City.